Association of renal function and symptoms with mortality in star fruit (Averrhoa carambola) intoxication. (9th August 2017) - Chua, Choon-Bing; Sun, Cheuk-Kwan; Tsui, Huan-Wen; Yang, Po-Jen; Lee, Kuo-Hsin; Hsu, Chih-Wei; Tsai, I-Ting
Abstract: Background: Star fruit (SF) is a commonly available fruit produced and eaten in tropical and subtropical countries. Since 1993, various reports have described neurotoxicity after eating SF, but this clinical condition remains unfamiliar. We aimed to describe this clinical entity, the role of renal dysfunction in this disorder, treatment strategies, and prognosis of patients with SF intoxication. Methods: We conducted a search of PubMed and Google Scholar databases from 1993 to 2016. We included reports describing patients with a clear history of SF ingestion with acute symptoms. We described the demographic characteristics, reported SF intake, treatments used, and outcomes. Results: We reviewed totally 126 patients (male:female = 1.5:1) from 33 articles with mean age 54.4 ± 11 (range: 30–84). The most common symptom was hiccups (65%), whereas confusion and seizure were the most common symptoms associated with mortality (42% and 61%, respectively). Pre-intoxication renal function also affected mortality. While there was no mortality in patients with normal renal function (NRF), the mortality of patients among reported cases with chronic renal insufficiency and end-stage renal disease undergoing dialysis were 36% and 27%, respectively. With the inclusion of patients reported to have NRF, the overall mortality was 24%. Consistently, the number of SF consumed was substantially higher in the patients with NRF than those with renal functional impairment. The most common treatment strategy was hemodialysis (59%). Conclusions: Patients with impaired renal function were at higher risks of SF intoxication. Severe neurologic symptoms mandate immediate medical intervention because of the association between their occurrence and high mortalities. Toxin removal through dialysis, rather than symptomatic relief, seems to be beneficial to patient survival. Early and continuous dialysis appears to alleviate severe symptoms and prevent symptom rebounds.